Membangun Kedekatan Guru dan Murid Dalam Proses Pembelajaran - Basith, Yudril (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This research aims to find out the importance of building close relationships between teachers and students in the learning process. This close relationship is one of the important factors in education that can have an impact on improving learning achievement, motivation and student involvement. This research uses the Systematic Literature Review (SLR) method. Data collection was taken from the source of scientific publication articles indexed in Google Scholar with the help of Harzing's Publish or Perish software application with the keyword “Teacher and student relationships” so that 500 papers were published in the 2001-2023 time period with a total of 13,659 citations, h-index 58, and g-index 93. Then the study focused on papers published in 2023 as many as 17 papers. Of the 17 papers, abstracts and related titles were read so that 6 papers were found that were relevant to the topic to be studied. Data analysis techniques in this study are planning, conducting and reporting. The study concludes that building close teacher-student relationships is essential in creating a comfortable, inclusive and supportive learning environment. This can be done by teachers with strategies to build emotional bonds, build a positive learning environment, personalized learning, and spiritual approaches, with humorous, dialogical, and interpersonal communication patterns. In building this closeness, there are several challenges and opportunities. Challenges that must be faced are personal differences and backgrounds, time constraints, effective communication, opportunities are knowing individuals deeply, listening and empathy, supporting and empowering, making connections with lesson content.